Developing a cloud based system for bird nests environment and behavior data monitoring and analysis, following the Internet of Things paradigm - Gamboa-Soto, Alexis (2020)
This work presents the design and development of a cloud based system prototype formonitoring birds in the wild, following the Internet of Things paradigm principles and tendencies.The behavior and population of birds represent an important metric to measure the health ofan ecosystem, becoming a very important tool to study the climate change influence on theenvironment. The system is built using NodeJs for the backend and a Cloud Computing Platformas a Service technology is utilized for the deployment to enhance the accessibility and scalability,while reducing operation and deployment costs. For this project, it is assumed the challengeof deploying the prototype without any monetary investment. The research main purpose isto set a real time bird nest monitoring web system, for environment and animal behavior datacollection and analysis, designed to define a communication standard for the integration fromcustom made devices utilized to collect the data, allowing for a better integration of differentcontraptions built to obtain wildlife data with minimum interference and giving enough dynamismwith stateless communication protocols to handle new data types from a wide variety of sensors.The standardization and centralization aims to solve the current issue of remotely collecting data